Improving investment risk management - Daribayeva, A.K.; Karbetova, Z.R.; Karbetova , Sh.R. (BUKETOV BUSINESS REVIEW, 2019)
The article discusses the theoretical issues of the risk management system: the value of risk for the economy, methods for assessing and analyzing risks. Particular attention is paid to the definition of objectives in risk management, as well as methods of risk assessment. Quantitative and qualitative risk assessment methods were studied and analyzed. The characteristics of the following main methods for estimating the probability of occurrence of risks are given: expert, statistical, computational, analytical, analog. The authors analyzed and assessed investment risk using the example of Smart Solution Company LLP, the main activity of which is the wholesale sale of goods. Based on the study, the following conclusion was made that the investment activity of Smart Solution Company LLP is carried out at a sufficiently high and effective level. Risk assessment of investment projects is carried out in full enough, however, in the process of assessing the risks of an investment event of Smart Solution Company LLP, an incompleteness was revealed both in the application of the available investment risk assessment methods and the incompleteness of the methods themselves. The conducted research allowed the authors to develop, in particular, the following proposals for improving the activity of Smart Solution Company LLP: creating their own company WEB site, opening an information terminal, developing an additional service.